2005
DOI: 10.1093/eurheartj/ehi618
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors, and outcomes of coronary dissections left untreated after drug-eluting stent implantation†

Abstract: This study, reporting for the first time on incidence, predictors, and outcomes of residual dissections in DES-treated coronary lesions, demonstrates their adverse clinical impact and supports the pursuit of a strategy of sealing dissection flaps with other DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 26 publications
4
64
0
2
Order By: Relevance
“…2,[10][11][12][13][14][15][16] In the stent era, one large angiographic study of 4630 lesions treated with DES reported a prevalence of 1.7%. 17 IVUS data showed that the prevalence of coronary artery dissection in lesions treated with balloon angioplasty was >60% 16,18 compared with 11% to 20% in lesions treated with bare metal stents [19][20][21] and 7.8% in lesions treated with DES. 22 In addition, the detection rates for coronary dissection varied among imaging modalities.…”
Section: Prevalence Of Coronary Artery Dissectionmentioning
confidence: 99%
“…2,[10][11][12][13][14][15][16] In the stent era, one large angiographic study of 4630 lesions treated with DES reported a prevalence of 1.7%. 17 IVUS data showed that the prevalence of coronary artery dissection in lesions treated with balloon angioplasty was >60% 16,18 compared with 11% to 20% in lesions treated with bare metal stents [19][20][21] and 7.8% in lesions treated with DES. 22 In addition, the detection rates for coronary dissection varied among imaging modalities.…”
Section: Prevalence Of Coronary Artery Dissectionmentioning
confidence: 99%
“…The importance of residual dissections in the DES era has been reiterated when observing an increased risk of ST (6.3% versus 1.3%; Pϭ0.01) and major adverse cardiac events (18.5% versus 11.2%; Pϭ0.07) at 6 months in patients with or without residual dissections. 48 ST is mediated predominantly by platelet-rich thrombi and hence platelet aggregation. ADP-induced (65Ϯ3% versus 51Ϯ2%; PϽ0.001) and shear-induced (40.9Ϯ12.2% versus 18.2Ϯ18%; Pϭ0.013) platelet aggregation has been found to be increased in patients with ST compared with control subjects, suggesting increased intrinsic platelet reactivity.…”
Section: Risk Factors Of Stmentioning
confidence: 99%
“…The greatest risk of antiplatelet therapy hyporesponsiveness occurs following PCI and stenting where HPR in the setting of ASA and ADP-receptor antagonist dual antiplatelet therapy (DAPT) is associated with a 2-fold increase in the risk of stent thrombosis 3,10 . Stent thrombosis is an infrequent but serious complication, which results in myocardial infarction rates exceeding 60%, case fatality rates ranging from 10 to 45% [11][12][13][14] , and increased long term MACE 15 . Several clinical factors including ACS presentation, body mass index (BMI) > 30 kg/m 2 , diabetes, and congestive heart failure (CHF) are associated with hyporesponsiveness to antiplatelet therapies 16 .…”
Section: Discussionmentioning
confidence: 99%